Graphic design and creativity in urban identity: The legacy of Nacho Padilla's posters to the city of Madrid - González Díez, Laura; Tabuenca Bengoa, María (Street Art & Urban Creativity, 2025)
This article aims to analyse Nacho Padilla's work as creative director of Madrid City Council during Manuela Carmena's term of office. This post, created during that legislature, had the objective of centralising all the creative projects, planning and supervising them in order to project a coherent visual and graphic narrative that would reinforce the capital's brand image. Padilla's work, a leading figure in the vibrant Spanish graphic design scene today, has left a very significant mark on the city of Madrid, especially through his contribution to the poster design of memorable campaigns such as those for San Isidro 2018 and 8M 2019. At a time when cities need to regain confidence and captivate both residents and visitors, public image and institutional campaigns play a decisive role in the strategy to revitalise urban life.